Podcasts in Production: An Examination of Current and Best Practices for Agricultural and Natural Resource Podcast Producers - Jacqueline Aenlle; Jamie Loizzo; Lisa K Lundy; J. C. Bunch; Kevin M Folta (Journal of Applied Communications, 2023)
Little research has been done on the production and use of podcasts in the fields of food, agriculture, natural resource, or human sciences (FANRHS). Currently, there is limited information for best practices on creating an effective FANRHS podcast to reach a target public audience. The purpose of this study was to examine existing practices and experiences of FANRHS podcast producers. The findings of this study will be of interest to organizations, institutions, and individuals who currently produce or are interested in producing an educational or science-based podcast. This study provided foundational information on podcast creation and maintenance. Future research should explore optimal podcast formats and content design to influence listeners’ perception and knowledge level on FANRHS science topics.
Keywords: science communication; adult learning; communication technology; podcasting; science education